Effect of the COVID-19 Outbreak on Patients with Oral Premalignant Lesions and Patients Requiring Maxillofacial Prosthesis in a Tertiary Dental Care Centre, Kerala, India: A Cross-sectional Study - Kala Sukumaran; Ashish Rajasekaran; Smitha Ravindran; Sheela Virginia Rodrigues; Gigi Thomas (Journal of Clinical and Diagnostic Research)
Introduction: Oral cancer is one of the most prevalent cancers in India. The implementation of preventive programs by the government has played a crucial role in improving patient prognosis through early detection. However, the nationwide lockdown imposed due to the Coronavirus Disease 2019 (COVID-19) pandemic significantly affected patients with non COVID-19 illnesses and disrupted preventive healthcare services and clinics operated by various government agencies. Aim: To compare the proportion of patients diagnosed with oral premalignant lesions among those screened one year before and one year after the COVID-19 outbreak in a tertiary dental care centre in Kerala, India. Materials and Methods: The present cross-sectional study was in the Department of Prosthodontics, Government Dental College, Alappuzha, southern Kerala, India, from April 2019 to March 2021, based on medical records. The proportion of patients diagnosed with oral premalignant lesions before the COVID-19 outbreak (group 1) (April 1, 2019, to March 31, 2020) was compared with the proportion of similar cases after the outbreak (group 2) (April 1, 2020, to March 31, 2021). Additionally, the proportion of patients rehabilitated with maxillofacial prostheses during the same period was analysed. Statistical analysis was conducted using the Shapiro-Wilk and Kolmogorov-Smirnov tests to assess data normality. Chi-square tests were performed to compare proportions, while an independent t-test was used to compare patient data before and after the COVID-19 outbreak. A p-value of <0.005 was considered statistically significant. Results: In group 1, 6030 patients were screened, of which 81 (1.34%) had premalignant lesions and 14 (0.232%) required maxillofacial prosthetic rehabilitation. While in group 2, 19,963 patients were screened, of which 145 (0.72%) patients presented with premalignant lesions and 27 (0.135%) patients required maxillofacial prosthetic rehabilitation. The analysis revealed no significant differences in the proportion of patients diagnosed with oral premalignant lesions among the total screened population before and after the COVID-19 outbreak (p-value=0.8829). Similarly, there was no statistically significant change in the proportion of patients rehabilitated with maxillofacial prostheses between the two periods (p-value=0.9567). Conclusion: The proportions of patients diagnosed with premalignant lesions among the total screened population and those rehabilitated with maxillofacial prostheses did not differ significantly before and after the COVID-19 outbreak.